The centre for leadership training, higher education leadership academy (AKEPT): assessing its relevance and achievements to the national higher education strategic plan (PSPTN) - Mohd Yusof, Danial; Abdul Rahman, Shukran; Zakariya, Hafiz; Shahadan, Md Azman (AKEPT, 2014)
The National Higher Education Strategic Plan and National Higher Education Action Plan or PSPTN (2007–2010) were launched in August 2007. These plans set out the transformation of higher education in Malaysia up to 2020 and beyond. The main agenda here is to produce graduates who are knowledgeable and competent in their fields, innovative, multilingual and technology savvy.